Skazani na komparatystykę i przekład - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2014)
There is no other way but comparative studies and translation studies The world we live in seems to be created for comparative-translation studies. There is real revolution, the change of system in the humanities and philology studies; there is the end of one world and the beginning of new digital era. Research methods and research themes are changing. On the one hand literature has lost its position in society and this is why a new formula of comparative studies cannot be limited to literature or culture but comparative studies must take into account non-artistic spheres of man’s activity; philology studies, if they want to survive, cannot be limited to exclusively literary, text oriented studies. On the other hand age of Internet, globalization, communication, transcultural society cannot function without translation which is the best way to get to know other cultures and enrich each other. The space between culture and languages, border zone which implies multiperspectivism seems to be the most appropriate for neo-philology studies and research. Key words: comparative studies, translation studies, reception, Croatian Studies abroad